Bentuk Mubazir Dan Kata Tidak Baku Pada Karangan Narasi Pengalaman Pribadi Siswa Kelas X IPS-3 SMA Negeri 1 Tunjungan Blora - Saputri, Dini Nur'ainy Gita; , Prof. Dr. Markhamah, M.Hum (2016)
Dini Nur'ainy Gita Saputri/A310120062. Bentuk Mubazir Dan Kata Tidak Baku Pada Karangan Narasi Pengalaman Pribadi Siswa Kelas X IPS-3 SMA Negeri 1 Tunjungan Blora. Skripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Agustus. 2016. This research aims to describe the form of redundant, said flip-flop, and the cause of ketidakbakuan sentence narrative essay students. This research is a qualitative research. The location of this study in SMA Negeri 1 Tunjungan Blora. The object of this study is fabricated IPS students of class X-3. Sources of data in this study were students of SMA Negeri 1 Tunjungan class X IPS-3. Methods of data collection methods refer to the technical note. Analysis of the data in this study using agih and dishonest. The results of this study are: first, in the essay students still found the use of the word is not raw. Not baku manifestation because it affected the local language, spoken language, spelling mistakes, and the absence of augmentation. Second, Errors due to redundant words are grouped into three, ie words that are synonymous, the statement said plural plus reset, and superlative statements with words so and all. Third, the cause of ketidakbakuan the sentence is due to the influence of the mother tongue, language spoken, no prefixes, and spelling mistakes. Keyword: Not baku, sentence redundant, not baku word cause